Effect of Carbonization Temperature on Properties of Char from Palm Kernel Shell - Sallau, Alhassan Adeku; Jauro, Aliyu; Kolo, Alhaji Modu; Hassan, Umar Faruq; Ekanem, Eno Okon (Journal of Science and Mathematics Letters, 2021)
The study investigates the effect of carbonization temperature of palm kernel shell (PKS) biomass, with a view to obtaining char suitable for electrode material. Char were obtained from palm kernel shell by carbonization at temperatures of 600, 800, 1000 and 1150 °C under inert condition for 60 mins each. The effect of carbonization temperature on proximate and ultimate, electrical conductivity, structural and morphological properties was investigated using the ASTM standard method for examination of coal and coke, elemental analyzer, four-point probe, x-ray diffractometer (XRD), Fourier transform infrared (FTIR) spectrometer and scanning electron microscope (SEM). The proximate analysis results showed the char yield to decrease from 29.68 % to 25.27 % as the temperature increases from 600 °C to 1150 °C. While the fixed carbon content in the raw sample was found as 22.22 %, it increases to 73.02 % in char obtained at 600 °C with highest value of 87.45 % obtained at 1150 °C. The volatile matter and moisture content values reduces with increase in temperature. An increase in carbonization temperature, also led to increase in elemental carbon content as well as improved electrical conductivity from 5.56 x 10-8 S/cm to 7.67 x 10-2 S/cm. Evidence of aromaticity and crystallinity towards graphitization was found from the FTIR and XRD analysis results. The results of electrical conductivity and XRD suggest possible use of the char obtained at 1150 °C for electrode material.